The suspension and interruption of administrative contracts in Spain as a result of COVID-19 - Junceda, Javier (2020)
The COVID-19 crisis has established various regulations to counteract the social and economic consequences it has caused. This is the case of the Spanish State, which during the pandemic has witnessed different formulations and modifications of its precepts, among them, the measures adopted to avoid the negative effects on employment and business viability derived from the suspension of public contracts. In this sense, this article will address the application and consequences of these new regulations, from a critical point of view.